MIRAGE Syndrome Caused by a De Novo c.3406G>C (p. Glu1136Gln) Mutation in the SAMD9 Gene Presenting With Neonatal Adrenal Insufficiency and Recurrent Intussusception: A Case Report - Chin, Xinyi; Sreedharan, Aravind Venkatesh; Tan, Ene Choo; Wei, Heming; Kuan, Jyn Ling; Ho, Christopher Wen Wei; Lam, Joyce Ching Mei; Ting, Teck Wah; Vasanwala, Rashida Farhad (Frontiers in Endocrinology, 2021)
Introduction Primary adrenal Insufficiency (PAI) presenting in the neonatal period can be life threatening and requires early recognition, diagnosis and management. PAI due to adrenal hypoplasia (syndromic/ non-syndromic) is a rare disorder. MIRAGE is a recently described syndrome with adrenal hypoplasia and multi-system involvement. Case Presentation A preterm female neonate presenting with primary adrenal insufficiency and persistent severe thrombocytopenia was diagnosed to have MIRAGE syndrome due to a de novo likely pathogenic variant c.3406G>C (p. Glu1136Gln) in the SAMD9 gene. In the first year of life, she had recurrent respiratory and gastrointestinal infection causing failure to thrive. At 17 months, she suffered recurrent intussusception requiring treatment with parenteral nutrition and high dose steroids. Subsequently, she established oral feeds with hydrolysed formula and demonstrated good weight gain. Conclusion In neonates presenting with PAI and associated multisystem involvement, a thoughtful approach and genetic testing is valuable in discerning an etiological diagnosis. This case of MIRAGE adds to the spectrum of reported cases and is the first to report on recurrent intussusception and its management with high dose steroids.